Dignity in the margins. Affective approaches to the informal city - Aubán Borrell, Mónica (Revista INVI, 2017)
The so-called affect theory seems to be unrelated to architecture. However, the recent exploration of informal cities challenges this idea. The incorporation of subjective variables, such as the life experience of those living in informal cities –regarded as key elements for urban projects–, enable us to take a close look to the notion of affect. This paper argues that current proposals associated with socio-spatial reconfiguration in informal Latin American cities create a close relationship between architecture and the affect theory, more specifically with its French post-structuralist branch, which acknowledges a key role played by the notions of territory and spatiality. This relationship is illustrated by two examples of concrete interventions: Jorge Mario Jáuregui, in Río de Janeiro and Urban-Think Tank, in Caracas. These cases show that theoretical-practical reflections and the concerns about community-based involvement lay the basis for the inclusion of affective variables into the understanding and production of inhabited territories.